CEDERA AKIBAT KEKERASAN TAJAM DAN TUMPUL PADA KORBAN PENGANIAYAAN: TINJAUAN FORENSIK BERDASARKAN PEMERIKSAAN VISUM ET REPERTUM - Rosmawaty Rosmawaty; Yosse Rizal; Rivanni Kurniawan; Maryeti Marwazi; Vina Tri Septiana (Yayasan Nusantara Hasana Berdikari, 2026)
Assault is a form of violence that can result in various types of injuries caused by sharp and blunt force trauma and has significant medical and medicolegal implications. Forensic examination through the identification and documentation of injury characteristics and the preparation of a visum et repertum plays an important role in providing an objective description of injuries sustained by victims. This article aims to analyze the characteristics of sharp and blunt force injuries in an assault victim based on forensic examination. The method used was a forensic case report using data obtained from a visum et repertum Pro Justitia. External examination of a 33-year-old male revealed multiple open wounds involving the head, forehead, upper extremities, lower back, and lower extremities, with characteristics consistent with sharp force trauma, as well as a bruise on the left eye consistent with blunt force trauma. Based on these findings, this case demonstrated multiple injuries resulting from a combination of sharp and blunt force trauma. Visum et repertum plays an important role in objectively documenting injury findings and providing medical information that supports the evidentiary process in assault cases.